ASPECTS OF DEVELOPMENT OF PROFESSIONAL GRAPHIC COMPETENCE OF STUDENTS USING THREE-DIMENSIONAL GRAPHIC PROGRAMS (Web of Teachers: Inderscience Research, 2024)
Three-dimensional graphics programs (3D graphics programs) currently play a large role in education, art, game design, animation, architecture and many other fields. Using these programs to develop students' professional graphic skills serves as an effective tool for strengthening their technical and creative skills. This article presents the main aspects of developing students' skills using 3D graphics programs.